If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(t + -8) + 50 = 10t + 15 + 2t Reorder the terms: 7(-8 + t) + 50 = 10t + 15 + 2t (-8 * 7 + t * 7) + 50 = 10t + 15 + 2t (-56 + 7t) + 50 = 10t + 15 + 2t Reorder the terms: -56 + 50 + 7t = 10t + 15 + 2t Combine like terms: -56 + 50 = -6 -6 + 7t = 10t + 15 + 2t Reorder the terms: -6 + 7t = 15 + 10t + 2t Combine like terms: 10t + 2t = 12t -6 + 7t = 15 + 12t Solving -6 + 7t = 15 + 12t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-12t' to each side of the equation. -6 + 7t + -12t = 15 + 12t + -12t Combine like terms: 7t + -12t = -5t -6 + -5t = 15 + 12t + -12t Combine like terms: 12t + -12t = 0 -6 + -5t = 15 + 0 -6 + -5t = 15 Add '6' to each side of the equation. -6 + 6 + -5t = 15 + 6 Combine like terms: -6 + 6 = 0 0 + -5t = 15 + 6 -5t = 15 + 6 Combine like terms: 15 + 6 = 21 -5t = 21 Divide each side by '-5'. t = -4.2 Simplifying t = -4.2
| 8e-(-2)=6 | | 4/9x^2=3 | | y-1/3=1/6 | | 9+5r+5r+2r= | | 30=1x-80 | | -1.4-2.7= | | 9(2x+3y)= | | 174=14.3*c*27 | | 4x-8=3y-15 | | 8h+20=69 | | 1-6(4-7x)=-23-3x | | 3(2x-5)-4x=5-4(7-x) | | 30=36a+6b+5 | | x/2-1=2x-7 | | 2(x-3)+21=-03 | | 7(x-8)-8(y+4)=80 | | -144/9 | | 30=36a+6b+c | | 27=4x+7(x-4) | | 2+-4+-5n-7+3n= | | 7x-9x+4=x-8+12 | | 2x-5(2x-10)=18 | | 8(8p+4)-8p=-27-3p | | 4g+8g+2g+9g+3g= | | 3x-5y=33-5x | | -16x-3y=12 | | 27w=-3w | | 456c=4 | | -15+5a=6a | | 10+x=5(x)+40 | | W-13.2=10.4 | | f(-6x)=6x^2-4 |